2016
DOI: 10.1016/j.socscimed.2016.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Increasing public support for food-industry related, obesity prevention policies: The role of a taste-engineering frame and contextualized values

Abstract: a b s t r a c tBackground: Support for policies to combat obesity is often undermined by a public sense that obesity is largely a matter of personal responsibility. Industry rhetoric is a major contributor to this perception, as the soda/fast food/big food companies emphasize choice and individual agency in their efforts to neutralize policies that are burdensome. Yet obesity experts recognize that environmental forces play a major role in obesity. We investigate whether exposure to a taste-engineering frame i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(79 citation statements)
references
References 49 publications
1
76
2
Order By: Relevance
“…[136,[156][157][158][159][160][161][162]), or on knowledge, attitudes, and beliefs about the causes, consequences and solutions to a range of health issues (n=25, e.g. [49,88,120,147,159,160,[163][164][165][166][167][168][169][170][171][172][173][174]). Such studies often employed experimental designs to test the impact of differences in framing (e.g.…”
Section: Exposure To News Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…[136,[156][157][158][159][160][161][162]), or on knowledge, attitudes, and beliefs about the causes, consequences and solutions to a range of health issues (n=25, e.g. [49,88,120,147,159,160,[163][164][165][166][167][168][169][170][171][172][173][174]). Such studies often employed experimental designs to test the impact of differences in framing (e.g.…”
Section: Exposure To News Mediamentioning
confidence: 99%
“…incorporating information on context, risk factors, prevention strategies, and social attributions of responsibility), increases support for policy change across a range of health issues, including obesity, smoking and diabetes [168], while another found that a taste-engineering frame (i.e. highlighting strategies used by the food industry to increase consumption), increases support for food and beverage policies [172]. In contrast, individualising the problem of obesity by identifying an individual child within a news story was associated with reduced support for obesity policies, regardless of how causes of obesity were framed [120].…”
Section: Exposure To News Mediamentioning
confidence: 99%
“…Humans (and their funding 'appendages') decide upon the "obstacles" worthy of overcoming. Patients, communities, and policy makers should be fully aware that while one scientist is working on the obstacles of infectious disease (e.g., vaccine development), another is using scientific reasoning to overcome the "obstacle" of how to make already-ultra-processed foods even more palatable [63,64].…”
Section: Narrative Medicine At Largementioning
confidence: 99%
“…This physiological form of engineering is accompanied by cognitive engineering in the form of effective marketing mentioned above-advertisements, celebrity endorsements, toy giveaways, "health-halo" label claims, and vague terminology such as "nutritious" which collectively appeal to the mind of the parent and/or child consumer. The third form of engineering is the manipulation of the total food environment via product placement and prominent shelf-space devoted to ultra-processed, energy-dense, low-nutrient foods [147].…”
Section: Engineering Policy Marketing Dysbiosismentioning
confidence: 99%